2022
DOI: 10.1371/journal.pone.0277929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt reduction interventions in lowering blood pressure: A comprehensive systematic review and meta-analysis of controlled clinical trials

Abstract: Background Excessive salt intake results in hypertension (HTN), which is a major risk factor for cardiovascular disease (CVD). This review and meta-analysis aimed to evaluate the effect of salt reduction interventions on systolic blood pressure (SBP) and diastolic blood pressure (DBP). Methods Studies were identified via systematic searches of the databases, including PubMed, Embase, Scopus, and Web of Science. All the studies examining the effectiveness of salt reduction interventions on blood pressure (BP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 119 publications
1
10
0
Order By: Relevance
“…It was estimated that a 0.4 gm/24 h sodium reduction would substantially reduce 9 million CVD events and save 4 million lives in the Chinese population by 2030 34 . The significant reductions of 2.67 mmHg in SBP and 1.39 mmHg in DBP identified in this meta-analysis are comparable to the findings of a recent meta-analysis, which found that health education interventions significantly reduced SBP and DBP by 2.8 and 2.1 mmHg, respectively 4 . Similarly, another meta-analysis found sodium reduction via dietary modifications reduced 2.9 mmHg in SBP and 1.2 mmHg in DBP 35 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It was estimated that a 0.4 gm/24 h sodium reduction would substantially reduce 9 million CVD events and save 4 million lives in the Chinese population by 2030 34 . The significant reductions of 2.67 mmHg in SBP and 1.39 mmHg in DBP identified in this meta-analysis are comparable to the findings of a recent meta-analysis, which found that health education interventions significantly reduced SBP and DBP by 2.8 and 2.1 mmHg, respectively 4 . Similarly, another meta-analysis found sodium reduction via dietary modifications reduced 2.9 mmHg in SBP and 1.2 mmHg in DBP 35 .…”
Section: Discussionsupporting
confidence: 86%
“…Excessive sodium intake (≥2 gm of sodium or equivalent to ≥5 gm of salt intake daily 1 ) is the leading dietary risk factor of hypertension (HTN) and cardiovascular disease (CVD) 1 , 2 , causing 1.65 million global deaths related to CVD annually 2 . The World Health Organization (WHO) recommends adults consume less than 2 gm of sodium daily 3 , as reducing sodium intake can lower blood pressure (BP) 4 , 5 , thereby reducing death and disability attributable to CVD 6 . However, most adults consume an average of 3.5–5.5 gm sodium daily 3 , which is significantly higher than the recommended amount.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high DBP levels among non-elderly individuals tends to lead to increasing SBP in the course of time, although it has not been evaluated fully that high DBP level as well as SBP causes cardiovascular diseases 24) . Additionally, a meta-analysis evaluated that the salt reduction interventions on BP led to a significant reduction in SBP among subjects aged 25-60 years 25) . It has been supposed that SBP had a stronger association with age and BMI than lifestyle factors except for salt reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The role of excessive salt intake in hypertension and the health benefits of salt reduction are very well documented [ 1 , 2 , 3 ]. Although sodium is essential for almost all physiological functions, from nutrient absorption to nervous impulse transmission and muscle contraction [ 4 , 5 , 6 ], in excess it adversely impacts the metabolism [ 7 ], immunity [ 8 ], fibrosis [ 9 ], and cardiopulmonary work [ 10 , 11 , 12 ] among many other effects.…”
Section: Introductionmentioning
confidence: 99%